2014
DOI: 10.2967/jnumed.113.131946
|View full text |Cite
|
Sign up to set email alerts
|

Midtreatment 18F-FDG PET/CT Scan for Early Response Assessment of SMILE Therapy in Natural Killer/T-Cell Lymphoma: A Prospective Study from a Single Center

Abstract: In a prospective study of newly diagnosed or relapsed histologically proven extranodal natural killer/T-cell lymphoma (ENKTL) patients, we aimed to determine the accuracy of midtreatment 18 F-FDG PET for response assessment using both visual and quantitative analyses. Methods: Twenty-four patients (12 men, 12 women; median age, 50 y; age range, 16-83 y) were referred for pre-, mid-(after 2-3 cycles of SMILE [prednisolone, methotrexate, ifosfamide, L-asparaginase, etoposide] chemotherapy), and end-treatment PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 23 publications
(37 reference statements)
5
41
1
Order By: Relevance
“…Recent reports from retrospective studies suggest that posttreatment PET/CT using the Deauville 5PS may be a valuable tool for response assessment in patients with newly diagnosed and R/R disease. [53][54][55] In a retrospective analysis of 102 patients with newly diagnosed ENKL, Deauville 5PS and EBV DNA after completion of initial treatment were independently associated with PFS and OS in the multivariable analysis. 54 Given the primarily extranodal sites of involvement often outside of the chest, abdomen, and pelvis, PET/CT is also preferred for followup to better assess these sites.…”
Section: Response Assessment and Additional Therapymentioning
confidence: 99%
“…Recent reports from retrospective studies suggest that posttreatment PET/CT using the Deauville 5PS may be a valuable tool for response assessment in patients with newly diagnosed and R/R disease. [53][54][55] In a retrospective analysis of 102 patients with newly diagnosed ENKL, Deauville 5PS and EBV DNA after completion of initial treatment were independently associated with PFS and OS in the multivariable analysis. 54 Given the primarily extranodal sites of involvement often outside of the chest, abdomen, and pelvis, PET/CT is also preferred for followup to better assess these sites.…”
Section: Response Assessment and Additional Therapymentioning
confidence: 99%
“…22 So far consensus has not been achieved on the positive and negative thresholds of Deauville five-point scale, recent studies have suggested the prognostic value of negative PET/CT response (DS 1-3) before ASCT for significant PFS and OS in patients with diffuse large B-cell lymphoma and follicular lymphoma. 23,24 In addition, for ENKTL patients, Khong et al 25 found that mid-treatment DS of 1-3 was a significant independent predictor of OS and PFS with 2-year OS and PFS rate of 81% and 62%, respectively. Our study used the cutoff value of Deauville score 1-2 to differentiate survival based on the statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Stage, surrogately detected by circulating EBV DNA plasma levels is of prognostic significance, [117][118][119] with chemoradiation regimens achieving 70-80% 5-year survival rates. 118,120 The outcome for plasmacytoma is better than multiple myeloma, with patients managed by localized radiation.…”
Section: Nut Carcinoma (Squamous Cell Carcinoma)mentioning
confidence: 99%